2018
DOI: 10.1016/j.idairyj.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the influence of metabolite diffusion on non-starter lactic acid bacteria growth in ripening Cheddar cheese

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This indicates that in the presence of higher concentrations of starter-lysate an increased growth may be expected, even under the limiting conditions as those found during cheese ripening. This is in agreement with Czarán et al (2018) who hypothesized that the availability and the level of nutrients released from SLAB are the main factors determining the rate of NSLAB growth during Cheddar cheese ripening.…”
Section: Effect Of Starter-lysate Concentration and Naclsupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that in the presence of higher concentrations of starter-lysate an increased growth may be expected, even under the limiting conditions as those found during cheese ripening. This is in agreement with Czarán et al (2018) who hypothesized that the availability and the level of nutrients released from SLAB are the main factors determining the rate of NSLAB growth during Cheddar cheese ripening.…”
Section: Effect Of Starter-lysate Concentration and Naclsupporting
confidence: 92%
“…This concept of cannibalism of SLAB by NSLAB was proposed by Thomas (1987) and it has been shown in other studies investigating the effect of sugars and amino acids in supporting NSLAB growth (Adamberg et al, 2005;Møller et al, 2020; J o u r n a l P r e -p r o o f Journal Pre-proof Ortakci et al, 2015;Saidi et al, 2020;Wallace and Fox, 1997). Czarán et al (2018) suggested that the concentration of nutrients released from SLAB is an important factor influencing the rate of NSLAB growth during cheese ripening.…”
Section: Introductionmentioning
confidence: 82%
“…On another experiment, it was reported that S. thermophilus Sfi39 and its three mutants had no lag phase, and the specific growth rate changed between 1.25 − 2.31 h −1 in M17 broth supplemented with 1% (w/v) lactose (LM17) at 42 °C (Zotta et al, 2009). These findings suggest that medium, temperature, and strain can influence the growth parameters (Czárán et. al., 2018).…”
Section: Growth Characteristics Of the Test Bacteriamentioning
confidence: 95%
“…Gradients within a single colony may be important in affecting the growth in different locations of a colony (Malakar et al, 2000(Malakar et al, , 2003, although the buffered environment of cheese may prevent the existence of pH microgradients, at least in microcolonies (Jeanson et al, 2013). Inoculum level may affect size and distribution of microcolonies and this, in turn, has been shown to affect cheese composition (Boucher et al, 2015a(Boucher et al, , 2015bJeanson et al, 2010), although, in the long term, it might not affect the distribution of small soluble metabolites implicated in some cross-feeding relationships SLAB and LAB, (Czárán et al, 2018) at least in internally ripened cheeses. (Callon et al, 2014;Eppert et al, 1997;Imran et al, 2010) effect: + stimulation of growth, = no effect, -inhibition/death; cost: 0 no cost, € metabolic cost, ?…”
Section: Confirming Interactions In Microbial Association Networkmentioning
confidence: 99%